Strategi Ustadz dalam Mengembangkan Self Esteem Santri di Pesantren - Moch. Ahsan; Junaidi Junaidi (Muthmainnah: Jurnal Bimbingan Konseling Islam dan Psikosufistik, 2025)
This study aims to explore the strategies used by ustadz (Islamic teachers) to develop students' self-esteem at Pesantren Al-Ma’ruf Kediri, a character-based educational context that remains under-researched. This research employs a qualitative method with a case study approach. The findings reveal that the ustadz implement an integrative and holistic strategy, manifested through positive communication and specific affirmations, personalized responsibility assignments, and the creation of an inclusive learning environment. The foundation of this entire strategy is the building of emotional closeness and direct role modeling, which creates a "safe haven" or a psychologically secure environment for the students. The combination of this structured psycho-educational approach and a warm relational approach forms an educational ecosystem that facilitates a profound transformation in the students. The implementation of this strategy successfully shifted the students' paradigm from a fixed mindset to a growth mindset, increased resilience, active participation, and social skills, and transformed the role of the ustadz from authoritarian figures to facilitators. These findings highlight that the pesantren environment, by integrating relational-affective and spiritual approaches, functions as an effective "social laboratory" for building authentic self-esteem—which stands on the pillars of competence and a sense of worthiness in the students.